(untitled) (Journal of Pathology of Nepal, 2019)
Background: Malaria is a major health problem especially in developing countries. It is a major cause of morbidity and mortality especially in the tropics. There are several hematological changes in this particular disease, which includes thrombocytopenia, anemia , atypical lymphocytosis and infrequently intravascular coagulation. The aim of the study is to detect and compare the severity of various hematological changes, especially thrombocytopenia in the particular type of malaria. Materials and Methods: This was an observational study done on the patients attending the outpatient and inpatient departments clinically suspected for malaria in Nobel Medical College, Biratnagar, Nepal. Thick and thin slides were made and stained with Leishman’s stain for malarial parasites and also antigen tests were included wherever necessary. Other tests included were, complete blood counts. Results: Amongst the included 800 patients with suspicion of malaria, 135 (17%) patients demonstrated malarial parasites on peripheral blood film. Male predominance in male to female predominance of 3.5:1 was observed. Total number of 120 out of 135 had thrombocytopenia. Thrombocytopenia was observed higher in P. Vivax (79.3%) followed by Mixed infection (17%) and P. falciparum (3.7%) respectively. Conclusion: Anemia with mainly thrombocytopenia was mainly seen in P. Vivax type followed by P. Falciparum. Since thrombocytopenia is associated with malaria, which is demonstrated in our study, treating physicians should keep malaria as one of the differential diagnosis in patients with fever and low platelets.